MEDIA JUGGLING: EXAMINING SMARTPHONE SECURITY BEHAVIOR AMID MEDIA MULTITASKING - Rajat Singh , Priyanka Soni , Rameez Manzoor , Surbhi Girdhar , Nandini Katare & Ashwati Chandran Nair (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2025)
Digital technology has made people marionette at its innumerable uses and advantages. The adaptation of technology over the past few decades has witnessed changes by manifold. The evolution of technology and the surge in the number of smartphone users globally pose a severe threat to the smartphone security of users. The attention that smartphone security requires might be diverted among the users of smartphones due to media multitasking. There is a need to study how smartphone users are linked with media multitasking to better understand the security of devices pertaining to human behavior. This study intends to examine the association of media multitasking with smartphone security behavior among people. The data from 338 respondents was employed in the study. The results of the study demonstrated that media multitasking significantly correlated with smartphone security behavior. Simple linear regression analysis showed that 1.9% of the variability in smartphone security behavior was due to media multitasking. In addition, this study discusses various aspects of media multitasking and smartphone security behavior.